Metode End User Computing Satisfication untuk Analisis Kepuasan Pengguna E-Learning MyCyber - Hendrawan, Satya Arisena; Muthmainnah, Syifa Nurlaeli (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
There is an error in the attendance recording, as well as a lack of notification features and replayable instructional videos. These issues impact user satisfaction and experience when engaging with the E-Learning of MyCyber. A study was conducted on the Indonesian Cyber University e-learning website to measure user satisfaction using the End User Computing Satisfaction (EUCS) method. Data collection was carried out through observation, literature review, and questionnaires. Partial analysis of user satisfaction from 80 active student respondents at Indonesian Cyber University revealed that 3 variables positively influenced user satisfaction: accuracy, ease of use, and timeliness, while content and format did not have a significant effect. Meanwhile, the simultaneous test results showed that the variables content, accuracy, format, ease of use, and timeliness influenced the satisfaction of users of the Indonesian Cyber University e-learning website by 83.8%. Recommendations for Indonesian Cyber University include improving and optimizing its e-learning website, particularly in content and information presentation, to enhance user satisfaction when using the E-Learning.